2002
DOI: 10.1016/s0925-4773(02)00394-5
|View full text |Cite
|
Sign up to set email alerts
|

The mouse rib-vertebrae mutation is a hypomorphic Tbx6 allele

Abstract: Rib-vertebrae (rv) is an autosomal recessive mutation in mouse that affects somite formation, morphology, and patterning. Expression of Notch pathway components is affected in the paraxial mesoderm of rv mutant embryos, and rv and a null allele of the Notch ligand delta1 show non-allelic non-complementation. By fine genetic mapping and complementation testing we have identified Tbx6, a gene essential for paraxial mesoderm formation, as the gene mutated in rv. Compound heterozygotes carrying a Tbx6 null allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 31 publications
2
55
0
1
Order By: Relevance
“…rv is a hypomorphic allele of the Tbx6 gene (Watabe-Rudolph et al 2002), which encodes a T-box transcription factor specifically expressed in the primitive streak/tailbud and presomitic mesoderm (Chapman et al 1996). To address how the complete loss of Tbx6 function affects Dll1, we analyzed Dll1 expression in embryos carrying a targeted null allele of Tbx6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rv is a hypomorphic allele of the Tbx6 gene (Watabe-Rudolph et al 2002), which encodes a T-box transcription factor specifically expressed in the primitive streak/tailbud and presomitic mesoderm (Chapman et al 1996). To address how the complete loss of Tbx6 function affects Dll1, we analyzed Dll1 expression in embryos carrying a targeted null allele of Tbx6.…”
Section: Resultsmentioning
confidence: 99%
“…Further support for this idea comes from our analysis of the mouse rib-vertebrae (rv) mutation, which represents a hypomorphic Tbx6 allele causing reduced Tbx6 expression (Beckers et al 2000b;Watabe-Rudolph et al 2002). Reduction of Tbx6 mRNA leads to altered abundance and distribution of mRNAs encoding the Notch pathway components Dll1, Dll3, Lfng, and Notch1 in the presomitic mesoderm, and to somite defects similar to mutations in Notch pathway components (Beckers et al 2000b).…”
mentioning
confidence: 93%
“…Somite formation can be rescued in these mutants with a Tbx6 transgene that is expressed at the correct time and place, but at lower levels than those observed in heterozygous mutant embryos (White et al, 2003). Although somites form at the correct time in the rescued mutants, the rostrocaudal patterning of the somites is defective, ultimately resulting in the fusion of the rib and vertebra, a phenotype also seen in the rib-vertebrae (rv) mutant in which the promoter of the Tbx6 locus is disrupted (Watabe-Rudolph et al, 2002;White et al, 2003). Taken together, these results show that Tbx6 is necessary for both the specification and the patterning of newly forming somites in the mouse.…”
Section: T-box Genes Regulate Paraxial Mesoderm Developmentmentioning
confidence: 99%
“…A ubiquitinated Nacke et al, 2000). Positional cloning of the rv mutation revealed that it was a Tbx6 hypomorphic allele (Watabe-Rudolph et al, 2002;White et al, 2003), and analysis of the promoter region of the Dll1 gene revealed binding sites for both the LEF1 and TBX6 transcription factors (Galceran et al, 2004;Hofmann et al, 2004; …”
Section: Figmentioning
confidence: 99%